2019
DOI: 10.5195/ijms.2019.355
|View full text |Cite
|
Sign up to set email alerts
|

The Weight of Schoolbags and Musculoskeletal Pain in Children of Selected Schools in Thimphu, Bhutan: A Cross-sectional Study

Abstract: Background: The carriage of loads on the back in children, >10% of one’s body weight (BW), induces postural change and morbidity related to spinal pain. We studied the weight of schoolbags and the prevalence of musculoskeletal pain related to carrying schoolbags among children in Thimphu, Bhutan. Methods: This was a cross-sectional study, with a multistage cluster sampling, conducted amongst grade 8 and 10 students. Data were collected using a standardized self-administered questionnaire and weights o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…Our study showed that the average of schoolbag weight in the whole population is close to what is reported by other authors. 9,27,35 Nevertheless, this value is higher than those found by Mwaka et al 1 , Dianat et al 19 , and Furjuoh et al 36 On the other hand, the value obtained in school children in the present study is lower than that reported by Ibrahim 31 and Dorji et al 37 This disparity in schoolbag weight in these different studies could be explained by differences in curricula in each country, by levels of development, and by behavioral and cultural differences between countries.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our study showed that the average of schoolbag weight in the whole population is close to what is reported by other authors. 9,27,35 Nevertheless, this value is higher than those found by Mwaka et al 1 , Dianat et al 19 , and Furjuoh et al 36 On the other hand, the value obtained in school children in the present study is lower than that reported by Ibrahim 31 and Dorji et al 37 This disparity in schoolbag weight in these different studies could be explained by differences in curricula in each country, by levels of development, and by behavioral and cultural differences between countries.…”
Section: Discussioncontrasting
confidence: 70%
“…more than 60%. 6,16,19,37 The analysis of the adjusted odds ratio showed that the risk of developing musculoskeletal symptoms was higher for school children in categories >10% to ≤15% and >15% and this in the French-speaking subsystem compared to the English-speaking subsystem (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A notable agreement in the literature pertains to the tolerable upper ‘threshold’ for load carriage in younger age cohorts being ~10–15%BM [ 2 , 3 , 9 , 45 ]. The current study appears to agree on the basis that those carrying loads above 15% were ~9 times more likely to report pain associated with bag carrying compared to those below the threshold.…”
Section: Discussionmentioning
confidence: 87%
“…Schoolbag carriage is a necessary component for most schoolchildren that, when excessive, can (i) compromise posture, (ii) induce neuro-musculoskeletal disorders, (iii) moderate cardiopulmonary function, and (iv) cause shoulder, back, and hand pain. The primary mediating factor for adverse reactions associated with schoolbag carriage is likely related to the actual mass of the schoolbag and, because of the nature of carrying, places most of the mechanical stress on the cervical vertebrae, shoulders, and lower back [ 1 , 2 , 3 , 4 , 5 ]. Heavy schoolbag loads are also typically associated with postural deviations such as posterior pelvic tilt [ 6 ], increased thoracic kyphosis [ 7 ], altered postural angles (e.g., cranio-vertebral angle [CVA], cranio-horizontal angle [CHA], sagittal shoulder posture [SSP], and lumbo-sacral angle) [ 8 , 9 , 10 , 11 , 12 ], increased forward trunk lean [ 13 , 14 , 15 ], changes in lung function [ 1 , 16 ], and changes in both gait kinetics and kinematics [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research in the field of musculoskeletal pain remains important as it can manifest as early as adolescence. For example, schoolchildren often experience musculoskeletal pain due to the weight of their schoolbags [34,35].…”
Section: Future Researchmentioning
confidence: 99%